Conversion of Recent-Onset Atrial Fibrillation or Flutter with Amiodarone after Ibutilide Has Failed: A Rapid, Efficient, and Safe Algorithm - Dilaveris, Polychronis; Synetos, Andreas; Giannopoulos, George; Gialafos, Elias; Stefanadis, Christodoulos (Annals of noninvasive electrocardiology, 2005)
Background: Ibutilide and amiodarone are used for the pharmacological conversion of atrial fibrillation (AF) or flutter (AFl), but their efficacy is rather moderate. Methods: To test whether the use of ibutilide as a first‐choice drug and of amiodarone as a second‐line treatment provides a rapid, effective, and safe algorithm for conversion of recent‐onset AF or AFl to sinus rhythm (SR), 85 consecutively recruited patients (59 women; mean age 69.7 ± 0.9 years) with AF or AFl of recent onset received 1 or 2 mg of ibutilide infusion. In the case of ibutilide failure, amiodarone was given (6 mg/kg IV infusion over 60 minutes followed by 1200 mg IV infusion over 24 hours) 4 hours later. Ten patients with AF or AFl of recent onset were used as controls. The maximum rate‐corrected QT interval was calculated in all patients and controls before the start of the study (baseline electrocardiogram (ECG)), 30 minutes later (30‐min ECG), and 4 hours later (4‐h ECG). Results: Fifty‐eight (68%) patients reversed to SR within the first 4 hours after the end of ibutilide infusion. In those 27 patients in whom ibutilide failed, amiodarone was given. Twenty‐four of them (28%) were converted to SR during amiodarone infusion. Therefore, in total, 82 (96%) patients with recent‐onset AF or AFl were converted to SR. The 10 controls were monitored for the same time period as the study patients and 5 (50%) out of them were spontaneously converted to SR (P < 0.0001). No pro‐arrhythmia or any other side effects were noticed in the study patients or in the controls. QTc was moderately decreased before the start of amiodarone infusion in patients group, while it did not differ among the three ECGs in controls. Conclusions: The combination of ibutilide as a first‐choice drug and of amiodarone infusion in the case of ibutilide failure provides an effective, rapid, and safe algorithm for restoration of SR in patients with AF or AFl of recent onset.